"It's Not a Case of He'll Be Home One Day." The Impact on Families of Sentences of Imprisonment for Public Protection (IPP). Issue 4 (2nd October 2019) - McConnell, Mark; Raikes, Ben
ABSTRACT: There is now a growing body of literature which is centred upon the negative outcomes that occur for many families, and by extension, children who experience the imprisonment of a father. Typically, families suffer the consequences of living with stigma and financial difficulties, while children are often affected by the accompanying secrecy and are provided with limited information about what has happened to their incarcerated parent. These factors can combine to increase the chances of children and family members in this position developing mental and physical health issues and other associated difficulties. Drawing on the findings from the lead author's research on the impact of indeterminate sentences of Imprisonment for Public Protection (IPPs) upon families, the authors will argue that for families where fathers are serving IPPs, the potentially negative effects of parental incarceration are considerably magnified. The evidence gathered suggested a worrying picture, as the unique nature of the IPP sentence has resulted in a severely detrimental impact upon families and children. With no definite release date, there is an absence of hope, which can quickly lead to despair for IPP prisoners and their families who have very little understanding of the gravity of their predicament.